Election Cycles and Organizations: How Politics Shapes the Performance of State-owned Enterprises over Time - Inoue, Carlos (Administrative Science Quarterly, 2020)
This study develops a dynamic perspective on how elected state officials’ political incentives shape the behavior and performance of organizations, particularly state-owned enterprises (SOEs). Drawing on theoretical views about the relationship between politicians and firms, I argue that state officials seeking votes manipulate SOEs to boost employment before elections. As a result, SOEs exhibit both higher employment levels and lower financial performance in election years. The positive relationship between elections and SOE employment, however, is not uniform across firms and geographic communities: it is likely to be stronger in economically disadvantaged communities and weaker for SOEs with private investors. Data from Brazil’s water sector—an industry managing a crucial societal resource—support these predictions. These results shed light on the mechanisms linking officials’ political incentives and SOE behavior and show that SOE performance is politically contingent and thus varies systematically over time. More broadly, this study reveals how firms’ responses to political pressures depend on both organizational and community attributes and highlights how the interplay of election cycles, organizations, and communities shapes the performance of organizations in state capitalism.